Global trends in hemophilic arthropathy research: a bibliometric and visualization analysis - Wei, Zhihao; Ou, Lijun; Chai, Sheng; Zhang, Dongdong; Tang, Gangjian (Frontiers in Medicine, 2025)
BackgroundHemophilic arthropathy (HA), a common complication of hemophilia caused by recurrent hemarthrosis, significantly impacts patients’ quality of life. Despite ongoing research, a comprehensive overview of research trends for HA is lacking. Therefore, this study utilizes bibliometrics and knowledge mapping techniques to visually analyze the current status and developmental trends of HA-related research, and analyzed and predicted future research hotspots.MethodsA bibliometric analysis was conducted using the Web of Science Core Collection database. Data on publications, author names, countries, research institutions, journals, and keywords were extracted and visualized using Bibliometrix, VOSviewer, and CiteSpaces.ResultsThe number of HA-related publications has increased steadily over time. United States was found to be the leading country in terms of publications and international collaborations. HEMOPHILIA was found to be the most influential journal and Hospital Universitario La Paz to be the leading institution conducting HA-related research. Rodriguez-Merchan EC was identified as the most prominent researcher in the field. Keyword analysis identified five main research clusters, namely, quality of life and management, pathogenesis, classification and functional assessment, replacement surgery, and ankle arthritis treatment.ConclusionThis bibliometric analysis provides a comprehensive overview of the research trends for HA. Future studies must focus on elucidating the underlying mechanisms of HA, developing early diagnostic biomarkers, and exploring personalized treatment strategies to improve patient outcomes. Our study offers valuable insights to researchers to facilitate the identification of emerging trends and prioritization of future research directions.